ADEPT - Abnormal Doppler Enteral Prescription Trial - McCormick Kenny; Kempley Steve; Dorling Jon; Leaf Alison; Mannix Paul; Brocklehurst Peter (BMC, 2009)
Abstract Background Pregnancies complicated by abnormal umbilical artery Doppler blood flow patterns often result in the baby being born both preterm and growth-restricted. These babies are at high risk of milk intolerance and necrotising enterocolitis, as well as post-natal growth failure, and there is no clinical consensus about how best to feed them. Policies of both early milk feeding and late milk feeding are widely used. This randomised controlled trial aims to determine whether a policy of early initiation of milk feeds is beneficial compared with late initiation. Optimising neonatal feeding for this group of babies may have long-term health implications and if either of these policies is shown to be beneficial it can be immediately adopted into clinical practice. Methods and Design Babies with gestational age below 35 weeks, and with birth weight below 10th centile for gestational age, will be randomly allocated to an "early" or "late" enteral feeding regimen, commencing milk feeds on day 2 and day 6 after birth, respectively. Feeds will be gradually increased over 9-13 days (depending on gestational age) using a schedule derived from those used in hospitals in the Eastern and South Western Regions of England, based on surveys of feeding practice. Primary outcome measures are time to establish full enteral feeding and necrotising enterocolitis; secondary outcomes include sepsis and growth. The target sample size is 400 babies. This sample size is large enough to detect a clinically meaningful difference of 3 days in time to establish full enteral feeds between the two feeding policies, with 90% power and a 5% 2-sided significance level. Initial recruitment period was 24 months, subsequently extended to 38 months. Discussion There is limited evidence from randomised controlled trials on which to base decisions regarding feeding policy in high risk preterm infants. This multicentre trial will help to guide clinical practice and may also provide pointers for future research. Trial registration Current Controlled Trials ISRCTN: 87351483